A Note on the Ipecac Plantation in North Bengal - Choudhury, K. C. Roy (Indian Forester, 1951)
The plant Ipecac is the source of a very important drug-emetine. The original home of the plant is Brazil but it has been successfully raised in Bengal and Burma. It is a typical tropical plant thriving in areas of high rainfall. There seems to be fairly bright future for the drug.